2021
DOI: 10.1111/jocn.16058
|View full text |Cite
|
Sign up to set email alerts
|

An integrative review of fatigue in adults with type 2 diabetes mellitus: Implications for self‐management and quality of life

Abstract: Aims and objectives To synthesise empirical studies on factors related to fatigue and its impact on diabetes self‐management (DSM) and quality of life (QOL) in adults with type 2 diabetes mellitus (T2DM). Background Fatigue is commonly reported in people with T2DM, a chronic condition that is highly prevalent worldwide. However, a holistic understanding of the consequences and factors related to fatigue in adults with T2DM is not well synthesised. Design This integrative review used Whittemore and Knafl's meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 56 publications
6
14
0
Order By: Relevance
“…Our results confirm findings from an earlier study that identified pain, poor health, depression, and tiredness as common internal barriers to exercise among persons with type 2 diabetes or persons at high risk for diabetes [36]. Fatigue is also considered as a barrier for diabetes self-management [37] which influences levels of physical activity in these patients. Pain and physical discomfort as outlined by our study participants were additional individually perceived barriers to physical activity.…”
Section: Discussionsupporting
confidence: 89%
“…Our results confirm findings from an earlier study that identified pain, poor health, depression, and tiredness as common internal barriers to exercise among persons with type 2 diabetes or persons at high risk for diabetes [36]. Fatigue is also considered as a barrier for diabetes self-management [37] which influences levels of physical activity in these patients. Pain and physical discomfort as outlined by our study participants were additional individually perceived barriers to physical activity.…”
Section: Discussionsupporting
confidence: 89%
“…In this review, a significant relationship was also determined between sleep quality and QoL, with patients categorized as 'poor sleepers' more likely than their counterparts to score poorly across several QoL domains (Lou et al, 2015;Vieira et al, 2008;Zhao et al, 2016). This is comparable to previous research demonstrating a similar link between fatigue and self-management (Kuo et al, 2022), and sleep quality and duration on glycaemic control (Lee et al, 2017), which are both critical to living well with diabetes.…”
Section: Discussionsupporting
confidence: 88%
“…from an earlier study that identified pain, poor health, depression, and tiredness as common internal barriers to exercise among persons with Type 2 diabetes or persons at high risk for diabetes [22]. Fatigue is also considered as a barrier for diabetes self-management [23].…”
Section: Discussionmentioning
confidence: 99%